A synthetic biological approach to reconstitution of inositide signaling pathways in bacteria. (August 2019) - Clarke, Bradley P.; Logeman, Brandon L.; Hale, Andrew T.; Luka, Zigmund; York, John D.
Abstract: Inositide lipid (PIP) and soluble (IP) signaling pathways produce essential cellular codes conserved in eukaryotes. In many cases, deconvoluting metabolic and functional aspects of individual pathways are confounded by promiscuity and multiplicity of PIP and IP kinases and phosphatases. We report a molecular genetic approach that reconstitutes eukaryotic inositide lipid and soluble pathways in a prokaryotic cell which inherently lack inositide kinases and phosphatases in their genome. By expressing synthetic cassettes of eukaryotic genes, we have reconstructed the heterologous formation of a range of inositide lipids, including PI(3)P, PI(4, 5)P2 and PIP3 . In addition, we report the reconstruction of lipid-dependent production of inositol hexakisphosphate (IP6 ). Our synthetic system is scalable, reduces confounding metabolic issues, for example it is devoid of inositide phosphatases and orthologous kinases, and enables accurate characterization gene product enzymatic activity and substrate selectivity. This genetically engineered tool is designed to help interpret metabolic pathways and may facilitate in vivo testing of regulators and small molecule inhibitors. In summary, heterologous expression of inositide pathways in bacteria provide a malleable experimental platform for aiding signaling biologists and offers new insights into metabolism of these essential pathways.